Stability of aqueous ferric oxide suspension - Moriyama, Noboru (Journal of colloid and interface science, 1975)
The effects of various types of surfactants and inorganic phosphates on the stability of aqueous ferric oxide suspensions have been examined. The stability was evaluated from sedimentation velocity data. At low concentrations the stability increases with concentrations of surfactants and inorganic phosphates, whereas at high concentrations it decreases remarkably with increase in concentration above a certain value, which depends upon chemical compositions and molecular weights of surfactants or inorganic phosphates. Both the absolute values of zeta potentials and the amounts of adsorption increase with increases in the concentrations. There exists a correlation between stability data and zeta potential data or adsorption data at low concentrations. Correlations between stability data and zeta potential data or adsorption data, on the other hand, do not exist at high concentrations. Marked decreases of the stability at high concentrations may be due to the depression of electrical repulsion owing to the compression of the thickness of the double layer. The stability data in the systems of 1-1 type surfactants such as sodium dodecyl-benzene sulfonate and sodium dodecyl sulfate can be explained by applying the D.L.V.O. theory qualitatively. The stabilities undergo the effects of pH, particularly in the systems of inorganic phosphates, when pH values of the systems are changed.